2008
DOI: 10.4103/0255-0857.40534
|View full text |Cite
|
Sign up to set email alerts
|

Detection of <i> Enterobacteriaceae</i> producing CTX-M extended spectrum β-lactamases from a tertiary care hospital in south India

Abstract: A total of 23 clinical isolates (15 Escherichia coli and 8 Klebsiella pneumoniae), resistant to cefotaxime and ceftazidime recovered during 2002 and 2003, were investigated for production of CTX-M extended spectrum β-lactamase (ESBL) by phenotypic and molecular methods. The presence of ESBL was tested by NCCLS phenotypic conÞ rmatory test using cephalosporin/clavulanate combination discs and E-test ESBL strips. Determination of MIC of cefotaxime and ceftazidime was done with and without the presence of clavula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 14 publications
5
13
1
Order By: Relevance
“…Dual FQ and blactam resistance is quite problematic, especially among immunocompromised patients. In agreement with other Indian studies, the majority of our ESBL/AmpC-producing E. coli exhibited a high level of resistance towards quinolone (93.1 %) and FQ (75 %), which would have therapeutic implications (Baby Padmini et al, 2008). Several reports have documented a strong correlation between qnrA prevalence and ESBL positivity in E. coli isolates, especially the CTX-M type (Jacoby et al, 2003;Mammeri et al, 2005;Lavigne et al, 2006), which could frequently be due to the presence of these resistance determinants on mobile genetic elements (Jacoby & Sutton, 1991;Partridge et al, 2001;Preston et al, 2003;Villa et al, 2000;Wang et al, 2003 The virulence potential and multiple drug resistance observed among the E. coli of non-B2 phylogroups further strengthens the claim that horizontal gene transfer might play a major role in the emergence of drug resistance among these originally avirulent/less virulent strains which can no longer be called 'innocent bystanders'.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Dual FQ and blactam resistance is quite problematic, especially among immunocompromised patients. In agreement with other Indian studies, the majority of our ESBL/AmpC-producing E. coli exhibited a high level of resistance towards quinolone (93.1 %) and FQ (75 %), which would have therapeutic implications (Baby Padmini et al, 2008). Several reports have documented a strong correlation between qnrA prevalence and ESBL positivity in E. coli isolates, especially the CTX-M type (Jacoby et al, 2003;Mammeri et al, 2005;Lavigne et al, 2006), which could frequently be due to the presence of these resistance determinants on mobile genetic elements (Jacoby & Sutton, 1991;Partridge et al, 2001;Preston et al, 2003;Villa et al, 2000;Wang et al, 2003 The virulence potential and multiple drug resistance observed among the E. coli of non-B2 phylogroups further strengthens the claim that horizontal gene transfer might play a major role in the emergence of drug resistance among these originally avirulent/less virulent strains which can no longer be called 'innocent bystanders'.…”
Section: Discussionsupporting
confidence: 92%
“…Among the E. coli isolates that harboured bla TEM , 65.9 % exhibited an ESBL phenotype, while all the bla CTX-M + isolates exhibited an ESBL phenotype. SHVderived ESBL enzymes were not detected in the present study, which is in agreement with other Indian studies (Baby Padmini et al, 2008;Alfaresi & Elkoush, 2010). Conversely, Sharma et al (2010) reported that 12 (48 %) of the 25 ESBL-producing E. coli isolates they studied possessed a bla SHV gene.…”
Section: Discussionsupporting
confidence: 92%
“…The data which has been presented here, demonstrates the presence of the CTX-M genes in this part of our country. A similar study from south India also reported the CTX-M genes as the predominant ESBL genes [10]. CTX-M was reported to be the most prevalent gene among the E.coli strains and the Klebsiella species in another similiar study, but their co-production was not reported [11].…”
Section: Discussionmentioning
confidence: 86%
“…Clinical isolates from urine (344), pus (109), blood (15), IV catheter tip/ central line tip (10), sputum (12) and body fluid (10) specimens were processed.…”
Section: Samplesmentioning
confidence: 99%
“…Sequencing of 4 isolates revealed the presence of CTX M-15. This was the first report identifying CTX-M type ESBL from clinical isolates of E. coli and K. pneumoniae from South India [24]. Grover et al [25] of New Delhi in 2006 reported the prevalence of TEM and SHV in ESBL producing Gramnegative bacteria to be up to 88.8 %.…”
Section: Iso-electric Focusingmentioning
confidence: 87%